The lymphocystis diseases in the Olive flounder, Paralichthys olivaceus - Hossain, Mosharrof; Kim, Seok Ryel; Oh, Myung Joo (University Journal of Zoology, Rajshahi University, 2008)
Lymphocystis disease virus (LCDV) is the causative agent of lymphocystis disease, affecting more than 100 teleost species worldwide. Characteristically, LCD is chronic, self limiting and species specific. The greatly hypertrophied cells, called lymphocystis tumor cells, typically occur on the skin, fins and oral region. Lymphocystis cells were ovoid to circular and varied in sizes ranging from 200-250 mm. The lymphocystis disease infected flounder have unsightly appearances that discourage the commercial values. A PCR detection technique was developed to amplify a fragment of LCDV major capsid protein gene (1347bp) which is shortcoming and useful. The PCR result proved that the LCD-virus replicated in the epidermis (fins and skin) not in the spleen, kidney, intestine or brain of Paralichthys olivaceus. Keyword: Lymphocystis disease, LCDV, PCR, Paralichthys olivaceus Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 59-62